Implementasi Teori Psikologi Humanistik dalam Pengembangan Kurikulum Pendidikan Agama Islam di Sekolah/ Madrasah - Qosim, Mohammad (Universitas Muhammadiyah Yogyakarta, 2024)
This research aims to describe humanistic learning theory and its implications for the development of the Islamic religious education curriculum. This research method analyzes data using content analysis, which is a scientific analysis examining previous articles. Research data was obtained from book and journal records. This qualitative research aims to determine the form of implementation of humanistic theory in developing the Islamic Religious Education curriculum in schools and madrasas. The results of this research are in the form of an understanding of humanistic learning theory and humanistic learning figures, including Abraham Maslow, as follows: a) Abraham Maslow's biography; b) Abraham Maslow's humanistic learning theory; c) Implications of Abraham Maslow's theory in developing the Islamic Religious Education curriculum. Rogers's flow of humanistic theory and its implications for Islamic religious education lessons. This research was conducted at the school with the aim of finding out how far the application of this theory has been beneficial for the development of student learning at school. In reality, teaching staff or teachers have more or less applied related humanistic theories in the development of Islamic religious education materials in order to increase students' sense of concern for their fellow students and the existing school environment.